Case Report: Monitoring neuromuscular fatigue through jump performance over two seasons in a cerebral palsy sprinter - Antunes, D.; Nascimento, E. M. F.; Rossato, M.; Silva, E. S. da; Lucas, R. D.; Fischer, G. (Frontiers in Sports and Active Living, 2025)
Introduction: World Para Athletics classifies athletes with brain injury, cerebral palsy, and motor coordination impairments into Group Class 31 to 38. Para athletes who can run and jump but are affected by impairments such as athetosis, ataxia, and dystonia, which impact all four limbs and the trunk, are categorized as Class T36. Monitoring training load and performance is essential for guiding training programs and preventing injuries in this population. Vertical jumps are commonly used to assess neuromuscular parameters in athletes with cerebral palsy. In this study, we tracked performance changes and monitored vertical jump height and power over two competitive seasons in a sprinter with cerebral palsy.